PENGELOLAAN RISIKO DALAM PENGGUNAAN DIGITAL PAYMENT ( STUDI KASUS KIDDY PLAYLAND ) - Saffa, Natasha Ardhia; Ariani, Mintarti; Budiarto, Bambang (FEB Universitas Sam Ratulangi Manado, 2024)
Consumer behavior in making digital payments has experienced significant acceleration in recent years, driven by technological developments and changes in consumer needs. The aim of this research is to determine the main factors that influence the use of digital payments and their impact on consumer behavior at Kiddy Playland. The research method used is correlational, namely by interviews and distributing questionnaires to digital payment users at Kiddy Playland. The analysis results show that ease of access, convenience and security are the main drivers for the use of digital payments for both consumers and business owners. Use is also able to change consumer financial behavior, especially in terms of personal financial management, spending patterns, and preferences for digital payment services. These findings have important implications for digital payment service providers and policy makers when developing strategies to increase entrepreneur productivity. Keywords: consumer behavior, digitalization, digital payment, purchase decision